Endophytic bacteria from Anysophyllea disticha (Raja Berangkat - Zainal Abidin, Zaima Azira; Shahari, Rozilawati; Mispan, Mohd Razali (2017)
The endophyte-plant interactions have been the subject of many studies among researchers to understand their full potential especially those that can contribute in drugs development. However, studies conducted on endophytes residing in local medicinal plants are still scarce. Thus, this study attempted to assess the endophytic bacteria present in roots and leaves of Anisophyllea disticha or locally known as Raja Berangkat. Anisophyllea disticha is a medicinal plant that has been used extensively by the locals to treat many diseases. Anisophyllea disticha collected in Tasik Kenyir was used in this study and was surface-sterilized prior to isolation on nutrient agar. A total of 40 representative endophytic bacteria were further identified and characterised through 16S rRNA gene sequences and biochemical profiles. Partial sequences of 16S rRNA gene of endophytic bacteria revealed that majority of the endophytic bacteria isolated from the leaf of Anysophyllea disticha belong to the genus Bacillus with the rest belonging to genera Paenibacillus and Aeribacillus. Similarly in root of Anysophyllea disticha, majority of the endophytic baceria were found to belong to genus Bacillus with the remaining belonging to genera Staphylococcus, Lysinibacillus, Paenibacillus and Mycobacterium. Further investigation on these potential endophytic bacteria may reveal its true potential that can be utilised in natural product discovery.